2016
DOI: 10.1589/jpts.28.1294
|View full text |Cite
|
Sign up to set email alerts
|

The effect of peculiar complex core balance training on isokinetic muscle functions of the knee and lumbus

Abstract: Abstract. [Purpose] This study aimed to investigate the effect of peculiar complex core balance training on the isokinetic muscle function of the knee joint and lumbus to provide fundamental data for establishing a training program that focuses on improving the performance and prevention of injury by developing the core and low extremity muscles. [Subjects and Methods] The participants in this study included a total of ten high school athletes involved in a throwing event for over five years. The subjects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Y-balance test is one of the tests which is widely and easily used to measure the balance performance of athletes in athletic performance laboratories. It was reported that the balance and strength of the athletes increased with balance trainings (Heitkamp, Horstmann, Mayer, Weller, & Dickhuth, 2001;Lee & Han, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Y-balance test is one of the tests which is widely and easily used to measure the balance performance of athletes in athletic performance laboratories. It was reported that the balance and strength of the athletes increased with balance trainings (Heitkamp, Horstmann, Mayer, Weller, & Dickhuth, 2001;Lee & Han, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of core complex training is to strengthen the muscles in the core and lower extremities in order to enhance performance and prevent injuries. Core complex training has been demonstrated to improve the knee and lumbar isokinetic muscle function in throwers [ 1 ]. The majority of sports actions require a strong core, which can be developed through core-stability, core-strength, and functional workouts [ 2 ].…”
Section: Introductionmentioning
confidence: 99%